Journal of the Association "Its inception and conditions of development" 1944-1946 Historical study: University of Wasit – college of Education - الموسوي, عباس فرحان ا; كوت, انتظار نجم (Journal of College of Education, 2018)
This paper deals with the history of the Association and its development conditions 1944-1946, The time frame for the study was set between 1944 and the date of its founding, while 1946 was the date of its Turn it off, Due to government pressure, and despite the short life of the Journal has had a broad resonance in the history of contemporary Iraq because of its treatments for all the general conditions.    The research consisted of a historical introduction, two papers, and a conclusion, The first topic focused on the study of the founding of the Cultural Association Journal in Baghdad in December 1943, and its goals and management, And its various activities in the dissemination of cultural, political, economic and social ideas and their treatment of the general situation in Iraq during the Second World War and beyond and limited to its inception, The second topic is the issue of the Journal of the cultural association and clarifying its objectives, directions, finances, printing, News sources, printing presses, technical level, volume, output, language and offices sold, which made it important Journal that received readers attention inside and outside Iraq.